Hilsa Transcriptome Datasets - Md. Arko Ayon Chowdhury; MD. Rakibul Islam; Al Amin; Sadia Noor Mou; Kazi Newaz Ullah; Abdul Baten; Mohammad Shoyaib; Amin Ahsan Ali; Farhana Tasnim Chowdhury; Md. Lifat Rahi; Haseena Khan; Md. Ashraful Amin; et al. (figshare, 2023)
A  transcriptomic catalog of Tenualosa ilisha (Hilsa shad), constructed by assembling RNA-Seq reads generated in the next generation sequencing (NGS) platform from different tissues including brain, gill, kidney, liver, and muscle collected from different aquatic habitats (fresh, brackish, and sea waters). De novo assembly of the sequences obtained from 46 cDNA libraries revealed 462,085 transcript isoforms that were subsequently annotated using the Universal Protein Resource Knowledgebase (UniPortKB) as a reference.
Keywords: Bioinformatics and computational biology not elsewhere classified